Survai Aedes Aegypti L. (Diptera: Cu I. Pengukuran Index Breteaulicidae) Di Yogyakarta - Sugeng Juwono, Sugeng Juwono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1974)
Keyword : Aedes Aegypti